The Correlation between Self-Awareness and Cognitive Learning Outcomes in Social Studies of Grade IV Students - Indah Purnamasari; Dian Mayasari; Rini Setyowati; Park Hae Woon (International Journal of Multi Discipline Science (IJ-MDS), 2023)
The objectives of this study are: (1) to describe the self-awareness of grade IV students; (2) to describe the cognitive learning outcomes of grade IV students; (3) to find out how much of a correlation between self-awareness and cognitive learning outcomes. The research used was correlation research with a quantitative approach. The population and samples in the study were all grade IV students. The sampling technique in this study was the saturated sampling technique. The sampling technique was saturated sampling when all members of the population are used as samples. Data collection techniques in this study used questionnaires and documentation. Data analysis techniques by calculating the percentage of questionnaire scores obtained, the average, and correlation analysis with regression using Pearson product-moment. The results showed that (1) the results of calculating the scores of each indicator, indicator 3, namely having a mandir attitude, had a percentage of 84%, while the lowest percentage, namely indicator 1, recognized one's feelings and behaviours by 60%. The overall percentage of the student's self-awareness questionnaire score was 76.9%, which means each indicator is in a good category; (2) students' social studies cognitive learning outcomes in the average data of student scores of 70.69 were well categorized; and (3) there was a significant correlation between self-awareness and cognitive learning outcomes of social studies students with tcount = 5.012 > ttable = 2.004, a correlation coefficient value (r) of 0.56 in the sufficient category, and a determinant coefficient of 31.39%.